The Residences of the Upper Silesia Haute Bourgeoisie: Their Typology and Functional Transformation - Majcher, Joanna (Turyzm/Tourism, 2001)
The article is an attempt to look at how the grand residences of the Upper Silesia haute bourgeoisie came into existence based on archival materials and field research. The author presents a typology of those residences and their distribution within the earliest industrialised area of Upper Silesia, as well as an a comparison with the similar process which occurred in the Łódź industrial area.